Conditional risk and predictability of Finnish stock returns - Markku Malkamäki (Bank of Finland, 1992)
This paper studies the driving forces of predictable variation in Finnish stock returns. The dynamics of Ferson and Harvey's (1991) methodology are extended and applied within the Sharpe-Lintner CAPM. We find that market risk is conditionally priced in the thin Finnish stock market. Most of the predictable variation of stock returns is attributed to the time-varying risk premium, which supports the hypothesis of rational behavior by Finnish investors in setting stock prices. However, the conditional residual term accounted for a larger part of the predictable variation of the stock returns than is found in the US market.
URN:NBN:fi:bof-201808021865
Keywords: 330